Bingo! One Health - Ms Daniela Ribeiro; Dr. Richard Marques; Prof. Dr Maria Fonseca; Prof. Dr Sónia Ferreira (International Journal of Infectious Diseases)
Introduction: The promotion of health and education are two of the seventeenth Sustainable Development Goals (SDGs) set by the United Nations. To this day, antimicrobial resistance remains a global public health challenge, with direct impact in Human, Animal and Environmental Health. As the number of infections associated with antimicrobial resistance increases on a global scale, the recently coined “One Health” concept aims to emphasize the relevance of conjoint efforts to prevent and control infections, as well as to monitor antimicrobial resistance. Having in mind the long road ahead in what comes to the prevention of antimicrobial resistant, it is of the utmost importance to continue to raise awareness about this subject through focused science communication strategies aimed at different population segments. Methods: In this study, we developed a communication strategy, using gamification to raise awareness about antimicrobial resistance. When applied to health communication, gamification has been shown to galvanize the mobilization of scientific concepts. We developed a Bingo game, applied to microbiology, with particular emphasis on the “One Health” concept. The game can be used either by children or adults, being the difference, the rules followed depending on the player's age. Results: It was our aim that this game reached as many players as possible with diverse profiles and from different backgrounds. So, it was presented to a wide range of public from fourth grade to high school students (aged between 9 and 18), universities university students and the general population. While playing, all of the participants were able to collect and apply key concepts in the field of microbiology, namely related to “One Health”. Discussion: Education should be understood and used as a tool for social transformation, and as a resource to achieve social, cultural and economic equity. An informed citizen is more prone to make rational, scientifically sustained and balanced decisions. The use of gamification as a science communication resource in formal, non-formal and informal settings has the potential to empower the population with a set of tools, which can allow them to deal and/or pro-actively participate in infection control.In this study, the use of a wide range of public allowed us to raise awareness at young ages, through the application of key concepts in the area of microbiology, demonstrating the active role that these students can have as citizens and also giving the possibility of transmitting these information for older generations. Conclusion: We believe that this game is an attractive tool to raise awareness on antimicrobial resistance and foster understanding of the “One Health” concept and its implications. The use of active and appealing strategies, often in relaxed environments, aimed at different audiences can ultimately contribute to mobilize citizens into making informed decisions.